Investigating the Effect of Entrepreneurship Development on the Relationship between Market Orientation, Total Quality Management and SMEs Performance in Kano - Halilu Bello Rogo; Mohd Noor Mohd Shariff; Muhammad Haroon Hafeez (International Journal of Supply Chain Management, 2018)
This paper investigates the effect of entrepreneurship development on the Small and Medium Enterprises (SMEs) performance in Kano. The issue of Market Orientation (MO), Total Quality Management (TQM) on the Small and Medium Enterprises (SMEs) performance in Kano state will be an interesting area of research as a centre of commerce in Nigeria. The paper sample consists of 8,286 of all the SMEs operating in Kano state. Out of which 367 questionnaires were administered to respondents concerning the MO and TQM to SMEs performance, 297 were returned. The numbers of the valid questionnaires are 291. The data were analyzed using Partial Least Square Structural Equation Modelling (PLS-SEM) to determining the effect of the variables of the study. The findings of the paper indicated that entrepreneurship development factors: MO and TQM promoting SMEs performance in Kano state. The results showed a statistically significant positive influence of both MO and TQM to SMEs performance. The finding provides the government, policy maker, SMEDAN and SMEs owners/ managers with the important variables of this MO and TQM to SMEs performance in Nigeria. This paper also made some recommendations for future research.